Control of seedling damping of caused by Rhizoctonia solani and Sclerotium rolfsii using onion broths - Rivera, Marta Carolina (2013)
Damping off is a frequent disease that kills seedlings. Cultural control is the only tool in organic crops to manage this disease, and only empirical information is available on the efficiency of plant preparations. This work evaluates the effects of fermented onion decoctions on the growth of Rhizoctonia solani and Sclerotium rolfsii and disease incidence. Broth (B) and sterilized broth (SB) were respectively obtained by boiling chopped yellow onions in water, and incubating for 14 days at room temperature, with or without subsequent sterilization. The pathogens were grown on PDA supplemented with B and SB at 1.7, 3.3, 8.3, 16.7 and 25% (v/v). Their growth was reduced by B at 8.3, 16.7 and 25%. Production of sclerotia by S. rolfsii was diminished by B, but stimulated by SB. Penicillium purpurogenum, P. simplicissimum and Aspergillus niger obtained from B behaved as antagonistic against both pathogens, showing antibiosis, competition and hyperparasitism in dual confrontations with them. Broth and SB at 10 and 50% were sprayed on chard (Beta vulgaris), tomato (Solanum lycopersicum), pepper (Capsicum annuum) and eggplant (Solanum melongena) seedlings cultivated in pathogen-colonized soil. Damping off incidence in B treatments at 50% was markedly lower than the observed for SB. It is concluded that B antifungal activity depends on its dilution and mycota. Broth sprays should be considered as a tool to control damping off in low-environment-impact crop production. Further studies are needed for a complete understanding of B chemical and microbiological components, as well as their changes during fermentation.